MODELUL CONCEPTUAL AL EVALUĂRII ADAPTIVE A NIVELULUI DE PREGĂTIRE A STUDENŢILOR - USM ADMIN (Moldova State University, 2008)
In this article it is offered a conceptual model of student's preparing level adaptive evaluation, which consists of the following units: training objectives, curriculum standard, training purport, technology of adaptive testing, model of taxo- nomic evaluation, measuring model, pedagogic monitoring and automated technology. There are recommended some means of the content specification in each unit. The implementation of this model in studying of university discipline "Basics of Computer Programming" brings effective contribution to the development of future specialists' abilities. The adaptive evaluation permits not only the affirmation of changes in students' acquisition, but also the effective leading of the forming process, due to the immediate feed-back.